History of Conflict Resolution in Europe – A Project Report - Peter Collin; Wim Decock; Nadine Grotkamp; David von Mayenburg; Anna Seelentag (Rechtsgeschichte - Legal History)
The four-volume Handbuch zur Geschichte der Konfliktlösung in Europa (Handbook on the history of conflict resolution in Europe) deals with the history of institutionalised and rule-based conflict resolution in judicial and extra-judicial forms. It covers the period from antiquity up to the recent past, and the articles take up central problems of conflict resolution or describe the development in specific European regions and states. This contribution provides information on the handbook project, the origins of which reach back to 2012 and came to a conclusion with the publication of the handbook in 2021. The article describes the debates on conflict resolution within the juridical field and offers information about both the central concepts and content of the handbook.